2021
DOI: 10.3390/s21124118
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Remote Sensing and Mexican Water Quality Monitoring System Using an Extreme Learning Machine

Abstract: Remote Sensing, as a driver for water management decisions, needs further integration with monitoring water quality programs, especially in developing countries. Moreover, usage of remote sensing approaches has not been broadly applied in monitoring routines. Therefore, it is necessary to assess the efficacy of available sensors to complement the often limited field measurements from such programs and build models that support monitoring tasks. Here, we integrate field measurements (2013–2019) from the Mexican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…Like any of the principal component input numbers, the penalty coefficient c and the kernel parameter g influence the accuracy of the model, so we used the verification function tunelsssvm for optimization. The results of optimization are shown in Figure 5 c,e,g,i [ 25 ].…”
Section: Results and Analysesmentioning
confidence: 99%
“…Like any of the principal component input numbers, the penalty coefficient c and the kernel parameter g influence the accuracy of the model, so we used the verification function tunelsssvm for optimization. The results of optimization are shown in Figure 5 c,e,g,i [ 25 ].…”
Section: Results and Analysesmentioning
confidence: 99%
“…Yet while RS is a useful tool for monitoring water quality parameters, it has not been meaningfully integrated into operational water quality monitoring programs. Existing water quality time series data were used in [ 75 ] and assessed the effectiveness of multiple RS data platforms and ML models in estimating various water quality parameters. The authors showed that some sensors are poorly correlated with water quality parameters, while others are more suitable for water quality monitoring tasks.…”
Section: The State Of the Art: Advances In Intelligent Waterbody Info...mentioning
confidence: 99%
“… More research needs to be carried out on analyzing the importance of input data to output predictions. See examples in [ 62 , 75 ], each detailed below. The authors in [ 62 ] systematically analyzed relative variable importance to show which sets of input data contributed to the ML models’ performance.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations